Comparison of the effect of Sumbawa honey and sucrose as extracellular cryoprotectants on viability, morphology, and phenotype stability of CD34+ hematopoietic stem cells from umbilical cord blood - Samuel Febrian Wijaya; Retno Lestari; Inna Rahmawati; Imelda Rosalyn Sianipar; Robby Nuraditya; Iqbal Fasha; Gita Pratama; Radiana Dhewayani Antarianto (Institut Teknologi Bandung, 2023)
Cryopreservation is a common practice for the long-term storage and maintenance of the quality of Hematopoietic Stem Cells (HSC) from Umbilical Cord Blood (UCB). Cryomedium containing 10% DMSO is the standard intracellular cryoprotectant agent (CPA) in HSC cryopreservation. However, DMSO is toxic to both cells and patients during transplantation. Therefore, the concentration of DMSO needs to be reduced by adding extracellular CPAs, such as sucrose or Sumbawa honey. The objective of this study was to compare the ability of Sumbawa honey and sucrose as extracellular CPAs to protect HSC CD34+ during cryopreservation. This in vitro study was designed using cryomedium consisting of 10% DMSO as a control, 5% DMSO + 5% Sumbawa honey, and 5% DMSO + 5% sucrose. The results showed that the cryoprotectant containing 5% DMSO + 5% Sumbawa honey had a positive effect and a significant difference (p<0.05) compared with 5% DMSO + 5% sucrose on the viability and morphology of HSC. However, the mean reduction in phenotype stability as indicated by the decrease in percentage CD34+ in the 10% DMSO (6.90 ± 8.60), 5% DMSO + 5% sucrose (10.60 ± 9.20), and 5% DMSO + 5% Sumbawa honey (8.60 ± 11.50) showed no significant difference (p>0.05). In conclusion, the combination of DMSO and Sumbawa honey was able to maintain the viability, morphology, and phenotype stability of HSC. Therefore, honey can be used as an alternative cryoprotectant for the cryopreservation of hematopoietic stem cells.